A study on factors that influence college students to join fraternities and sororities - Job, Charlotte V.; Llamas, Ronand L.; Recabar, Sharoe S.; Trocho, Marigold Joy C. (2006)
Fraternity and sorority organizations nowadays can be considered a common scenario in every university. Though some rules and regulations may restrict their activities, more and more students especially in their college years engage themselves with these associations. In line with this, the researchers conducted this study to be able to know and to gain awareness of the driving factors or plainly the reason why college students join fraternities and sororities. The researchers identified major factors that can induce college students to join in fraternal or sororial groups. These can be categorized into three, the personal factors, the socio-economic factors, and the perceived benefits based on observation of actual practices of each organization, taking a view of an interested college students. Under the personal factors, gender and year-level were viewed to be an influencing factor, while for socio-economic actors, distance from home, financial status, family affiliation and peer pressure were identified to have encouraged college students to join fraternity and sorority. with regards to perceive benefits, this factor usually ranges from leadership training, socialization, local family, opportunities and the experience of a sense of brotherhood and sisterhood. The researchers obtained their primary data by conducting a survey. Questionnaires were developed and distributed to fraternity and sorority members in order to confirm the previously formulated hypothesis. The researchers also gathered additional relevant information through inquiries with University Offices and non-participant observations. Based on the findings accumulated and analysis of such, the researchers found out that personal factors and most of the socio-economic factors were not conclusive reasons why college students join fraternities and sororities. However, family affiliation or experiencing a second home or local family, in the company of co-members generally induces college students to associate themselves with frasorities. The results of the finding also apply to the perceived benefit that may be acquired if a student is a member of one particular organization. This proves that, students look more on the intangible benefits specifically emotional security and personal development. Findings also revealed that fraternity and sorority members are independent in mental attitude in the process of making their decision to join a certain organization. Only one of the hypotheses was positively confirmed, that is, perceive benefits encourage college student to join frasorities. One f the researchers' sanctions was also found correct which is the idea that they join because of the belief that doing so will help improve their personalities. Based on the summary of analysis, the researchers recommended the continuous good deeds of the organization in being socially responsible to community services. Everything resides on the quality of life, on ones personal orientation and on how a person reacts on various situations that he or she may face in life. The researchers formulated recommendations for those who are currently members, non-members and school authorities by referring to established laws or to actions as viewed to be socially correct and accepted.
[Research Paper] (BA 200 - Business Research) -- Iloilo City : UPV-CM, March 16, 2006.